Synthesis of intrathecal interferon in systemic lupus erythematosus with neurological complications. Issue 6400 (22nd October 1983) - Lebon, P; Lenoir, G R; Fischer, A; Lagrue, A
Abstract : Intrathecal synthesis of interferon in the absence of viral or bacterial infection was detected during the occurrence of neurological complications in two patients with systemic lupus erythematosus. The interferons displayed characteristics similar to those observed in the sera of patients with the disease. No interferon inducing activity was detected in the cerebrospinal fluid or serum of the two patients. These observations support the hypothesis of a localised mechanism of interferon induction in systemic lupus erythematosus which includes the interaction of lymphocytes with damaged tissues.